New Enviromental Paradigm (NEP) Differences Student with Field Independent and Field Dependent Cognitive Style - Natasia, Disa; Azrai, Eka Putri; Ernawati, E (Universitas Negeri Jakarta, 2015)
Student perspective on the environment and the factors that can influence it is important to be known. Student perspective on the environment can be determined by measuring the New Environment Paradigm (NEP). New Environmental Paradigm is a new perspective on the environment that reflects a better concern for the environment. New Environmental Paradigm owned by students can be different from one another are assumed to be influenced by cognitive style. Cognitive style is divided into field independent and field dependent. The purpose of this study was to determine the differences in the New Environmental Paradigm student with a cognitive style of field independent and field dependent. This research was conducted at the State University of Jakarta on June 2015. The method used is ex post facto. Samples are 82 students of 2014 biology class using the Slovin formula with simple random sampling technique. The test results prerequisite to Kolmogorov-Smirnov (Î± = 0.05) and Levene (Î± = 0.05) showed normal data and homogeneous. t test results (Î± = 0.05) showed that there is a difference in the average score of the New Environmental Paradigm (NEP) student with field independent and field dependent cognitive style. Results of this study have implications for academic practitioners to provide the most effective strategies to convey information in an attempt to fix the student perspective on the environment through Environmental Science subjects.